Preparation and performance evolution of enhancement polystyrene composites with graphene oxide/carbon nanotube hybrid aerogel: mechanical properties, electrical and thermal conductivity. (September 2021) - Xu, Hui; Song, Guojun; Zhang, Lina; Zhao, Zetian; Liu, Zhitao; Du, TingTing; Song, Junhao; Yang, Yanhui; Cheng, Yonghui; Wei, Yalong; Li, Xiaoru
Abstract: Graphene oxide/carbon nanotube aerogel (GOCA) with honeycomb three-dimensional framework is an ideal reinforcement material which can significantly improve the dispersion in the polymer matrix, and enhance the mechanical properties, thermal and electrical conductivity of the composites. In this work, large-size GOCA and GOCA/polystyrene (GOCA/PS) composite sheet were prepared via critical drying and in-situ polymerization, respectively, and the standard splines of mechanical properties were tested. The results indicated that the tensile, flexural, compressive, and impact strengths of GOCA/PS composites increased with the increase of GOCA content. When the GOCA content was 1.1 wt %, the above mechanical properties increased to the maximum, increased by 103.29%, 60.30%, 177.03%, and 611.38%, respectively. However, as the content of GOCA increased, the electrical conductivity and thermal conductivity showed an increasing trend. In addition, the synergistic enhancement mechanism between GO and CNTs has also been studied. We believe that the present method may provide an effective route for the design and investigation of reinforced composites. Highlights: 3D large-scale GOCA and GOCA/PS were prepared. The mechanical properties, electrical conductivity and thermal conductivity of the GOCA/PS nanocomposites were remarkably improved. The enhancement mechanism was explained.